Attitudes toward mental illness among college students in Nuevo Leon, México = Actitudes hacia las enfermedades mentales en estudiantes universitarios de Nuevo León, México - Vega Santiago, Irma Y.; González Santiago, Omar (Universidad Autónoma de Nuevo León, 2016)
Stigma associated with mental illness has detrimental effects on the treatment and prevention of these diseases. The aim of this study was to analyze attitudes toward mental illness in a sample of university students in Nuevo Leon, Mexico. Results. Nine hundred and forty-three students were surveyed, 66.9% believe that genetic and familial factors are the cause of mental illness. Among 20-30% believe that people with mental illness are a nuisance for people; between 12-14% would be ashamed of having a family member with mental illness and people know it; and 61.8% would be able to maintain a friendship with a person who have mental illness. Conclusions. Over 50% of respondents have favorable attitudes towards patients with mental illness and less than 30% attitudes of social distancing.